P104 Sensations associated with experimentally evoked cough: influence of low dose morphine sulphate in opioid responders. (15th November 2017) - Mitchell, J; Al-Sheklly, B; Issa, B; Collier, T; Sen, S; Ford, J Webber; Corfield, D; Smith, JA
Abstract : Introduction and Objectives: Patients with chronic cough complain of a variety of sensations that they perceive as provoking coughing, identifying irritation, tickle and the urge to cough (UTC) as important. Effective therapies for chronic cough such as low dose morphine have failed to reduce experimentally evoked cough responses, but their effect on the sensations driving cough is unknown. We hypothesised that low dose morphine therapy reduces the sensations driving cough and predicted that the sensations experienced during inhalational cough challenge may demonstrate this mechanism. Methods: Twenty-two refractory chronic cough patients (mean age 61.7 years, 18 female, mean cough duration 14 years) taking low dose morphine sulphate treatment enrolled into a double-blind randomised controlled crossover trial comparing the effects of low dose morphine sulphate with matched placebo. Following withdrawal of their morphine therapy, participants were randomised to receive morphine (5–10 mg BD slow release) or matched placebo during two treatment period (5–7 days duration) separated by a 5–7 day washout. On the final day of each treatment period subjects inhaled increasing concentrations of citric acid (0.01–4 M, 18 ascending concentrations), rating irritation, tickle, UTC and taste on 100 mm visual analogue scales (VAS; 0 mm=none and 100 mm=worst) after each inhalation. The challenge continued until subjects coughed at least twice on any concentration of citric acid (C2). For the analysis, general estimating equation (GEE) models evaluated the effect of treatment on reported sensations, with increasing per citric acid dose. Results: Compared with placebo, low dose morphine significantly reduced the VAS scores for tickle and irritation during the citric acid challenge (p=0.021, p=0.039), however UTC, taste and the number of coughs evoked were not improved (p=0.105, p=0.167, and p=0.337). Of particular note, morphine had no significant impact on C2 compared with placebo (p=0.611). Conclusions: This data shows that treatment with low dose morphine significantly reduces the noxious sensations driving cough. The effects on tickle and irritation appear more important than any impact on the UTC, numbers of coughs triggered or the traditional C2 endpoint, suggesting that reducing somatic sensations may be an important component of the mode of action of opioids in the treatment of cough.